Introduction to the Sociology of Organizations and Classical Organization Theory: A Perspective on Max Weber’s Bureaucratic Theory - Sri Devi Okta Viani; Elvi Rahmi Syukrina; Yunita Y; Akdila Bulanov (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Organizational sociology is a branch of sociology that examines organizations as a form of human cooperation in social life. Organizations have rules, structures, division of tasks, and relationships between members aimed at achieving common goals. In the development of organizational theory, one of the most well-known theories is Max Weber's bureaucratic theory. Weber explained that organizations will run more orderly if they have clear rules, a definite division of tasks, and a well-structured job structure.